The Content Analysis of Amino Acids in Auricularia auricula from Heilongjiang and Jilin. (27th November 2021) - Cui, Lili; Feng, Guoquan; Lu, Jie; Li, Changqin
Abstract : The content of amino acids in Auricularia auricula was analyzed by the method of acid hydrolysis and automatic online analysis. The content of total amino acids in A. auricula produced in Heilongjiang was between 68.287 and 110.949 mg/g, and the average was 90.848 mg/g. The content of essential amino acids in A. auricula from Heilongjiang was between 28.847 and 45.757 mg/g, and the average was 37.987 mg/g. The proportion of essential amino acids (EAA) to total amino acids (TAA) in A. auricula from Heilongjiang was between 41.24% and 42.26%. However, the content of total amino acids in A. auricula from Jilin was between 71.716 and 124.143 mg/g, and the average was 94.318 mg/g. The content of essential amino acids in A. auricula from Jilin was between 29.775 and 52.063 mg/g, and the average was 38.498 mg/g. The ratio of essential amino acids (EAA) to total amino acids (TAA) in A. auricula from Jilin was between 39.75% and 41.94%. The content of total amino acids and essential amino acids in A. auricula from Jilin was higher than that from Heilongjiang. However, EAA/TAA in A. auricula from Heilongjiang was higher than that of Jilin. The content of total amino acids in different batches of A. auricula in the same production area was quite different, but the ratio of essential amino acids content to total amino acids content was basically the same.